Development of djenkol peel extract-loaded liposome as functional food ingredients: Physicochemical characteristic, antioxidant activities, and cytotoxicity - Lalita Chotphruethipong; Sirima Sinthusamran; Soottawat Benjakul; Theeraphol Senphan; Sitthipong Nalinanon; Chodsana Sriket (Journal of Agriculture and Food Research, 2025)
Djenkol peel is an agricultural by-product containing valuable bioactive compounds. The direct use of its extract faces challenges related to stability and sensory acceptance. This study aimed to investigate the effect of djenkol peel extract (DPE) on the encapsulation efficiency (EE) using liposomes. The physicochemical properties, antioxidant activities, and cytotoxicity of the obtained liposomes were evaluated. DPE (0, 0.25, 0.50, 0.75, and 1.00%, w/v) was encapsulated using phospholipid/cholesterol as the wall material. The highest EE (66.69%) was observed in the liposomes loaded with 0.25% (w/v) DPE (LE-0.25DPE) ( P < 0.05). All DPE-loaded liposomes displayed nanometer-scale particle sizes (78.94-135.60 nm) and negative zeta potentials (-52.60 to -57.50 mV). Encapsulation of DPE in liposomes can mask its undesirable color. Fourier-transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), and differential scanning calorimetry (DSC) revealed changes in the physicochemical and thermal properties of LE-0.25DPE. Additionally, LE-0.25DPE showed increased DPPH radical-scavenging activity (DPPH-RSA) and ferric-reducing antioxidant power (FRAP) in a dose-dependent manner (250-2000μg/mL). In Caco-2 cell viability tests, LE-0.25DPE at 0.1-1μg/mL concentrations exhibited no cytotoxicity compared to the control ( P < 0.05). Thus, DPE-loaded liposomes demonstrate potential as a functional food ingredient with high bioactivity. Physicochemical characterization, antioxidant activities, and cytotoxicity of djenkol peel extract-loaded liposome • DPE-loaded liposomes enhance potential of djenkol peel extract as functional ingredient. • LE-0.25DPE shows optimal properties: 66.97% encapsulation, 78.94 nm size, -57.50 mV. • LE-0.25DPE exhibits strong, concentration-dependent DPPH radical scavenging activity. • Liposomal encapsulation masks DPE's color while preserving bioactive properties. • LE-0.25DPE shows minimal cytotoxicity on Caco-2 cells up to 100 μg/mL concentration.
Keywords: Phytochemicals and Antioxidant Activities; Food Chemistry and Fat Analysis; Proteins in Food Systems